Employee motivation and its impact on employee loyalty - Wan Omar, Maznah; Jusoff, Kamaruzaman; Hussin, Harniyati (IDOSI Publications, 2010)
When change and restructuring in an organization becomes inevitable, employee loyalty and their motivation becomes one of the major challenges currently facing most companies in the present world of business. On top of the ongoing focus on recruiting new talent, a further challenge lies in ensuring existing staff are focused, engaged and thus retained. Good organizations understand that loyal employee will result in a better business performance, so many are placing greater emphasis on measuring employee loyalty and how to motivate them in order to keep their staff happy. The purpose of this study is to identify the factors influencing employee motivation which will leads to employee loyalty towards their organization. The methodology uses in this research is through the distribution of a set of questionnaire to one hundred and eighty five respondents. Results from this study will be practically significant to practitioners and academicians in providing them with information on the most effective ways on how to manage their employees.